Epstein-Barr Virus-Negative Post-Transplant Lymphoproliferative Diseases: Three Distinct Cases from a Single Center - Şule Mine Bakanay; Gülşah Kaygusuz; Pervin Topçuoğlu; Şule Şengül; Timur Tunçalı; Kenan Keven; Işınsu Kuzu; Akın Uysal; Mutlu Arat (Turkish Journal of Hematology, 2014)
Three cases of Epstein-Barr virus (EBV)-negative post-transplant lymphoproliferative disease that occurred 6 to 8 years after renal transplantation are reported. The patients respectively had gastric mucosa-associated lymphoid tissue lymphoma, gastric diffuse large B-cell lymphoma, and atypical Burkitt lymphoma. Absence of EBV in the tissue samples was demonstrated by both in situ hybridization for EBV early RNA and polymerase chain reaction for EBV DNA. Patients were treated with reduction in immunosuppression and combined chemotherapy plus an anti-CD20 monoclonal antibody, rituximab. Despite the reduction in immunosuppression, patients had stable renal functions without loss of graft functions. The patient with atypical Burkitt lymphoma had an abnormal karyotype, did not respond to treatment completely, and died due to disease progression. The other patients are still alive and in remission 5 and 3 years after diagnosis, respectively. EBV-negative post-transplant lymphoproliferative diseases are usually late-onset and are reported to have poor prognosis. Thus, reduction in immunosuppression is usually not sufficient for treatment and more aggressive approaches like rituximab with combined chemotherapy are required.